THE INFLUENCE OF VILLAGE FUND ACCOUNTABILITY AND TRANSPARENCY ON PUBLIC TRUST - Aliah Tri Saniyah; sahrullah; Asriani Hasan (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2025)
This study aims to analyze the influence of accountability and transparency in village fund management on the level of public trust in Kading Village, Barru Regency. Using a quantitative approach, data were collected through questionnaires and analyzed using multiple linear regression. The results showed that partially, accountability has a positive and significant effect on public trust, indicating that clear accountability increases the credibility of the village government. Similarly, transparency has a positive and significant effect, indicating that public information disclosure strengthens public trust. Simultaneously, accountability and transparency have a significant effect with an Adjusted R Square value of 0.531, meaning that both variables contribute 53.1% to public trust. These findings confirm that the integrated implementation of good governance principles is crucial in building the legitimacy of village government. The village government is advised to continue to improve the accessibility of APBDes information, while future researchers can develop this model by adding variables such as apparatus competence or community participation.